Cost-Benefit Evaluation: Students', Faculty's, and Staff's Willingness to Pay for a Campus Safety App. Issue 2 (3rd April 2017) - Yabe, Manako
Abstract : Many universities began to explore possibilities of launching campus safety apps beyond blue light emergency towers to improve campus security. However, no previous studies exist regarding whether the apps have more benefits beyond their annual fees, compared to their annual fees of blue light emergency towers. This study conducted a choice experiment to measure students', faculty's, and staff's marginal willingness to pay for a campus safety app at a large public university in the United States. As a result, a total of these groups' values of the app was shown to be at least 30, 205 per year. This result indicated that their values were three times larger than the actual annual fee of the campus safety app, and cost-effectiveness compared to blue light emergency towers.